Relationship between personality traits, gender, and passive and active social media use among Singaporeans during COVID-19 circuit breaker - Lee, Cherie Ming Xuan (Nanyang Technological University, 2021)
Social media platforms are increasingly popular and universally used, allowing users to experience online interactions, entertainment, and to seek information. The behaviours that users engage in when using the different features of social media platforms can be categorized into passive and active social media use. As individual differences such as personality traits and gender may influence one’s social media use, past studies have explored the relationship among the variables. However, results were inconclusive and there is a lack of findings on passive and active social media use as well as for populations outside of Europe and America. As such, this study aimed to explore the relationship between personality traits, gender, and the passive and active social media use among Singaporeans across three platforms - Facebook, Instagram, and Twitter. During the COVID-19 Circuit Breaker period, participants completed an online questionnaire measuring personality traits and the frequency of different social media behaviours. Data from 135 participants were analysed using correlational analysis, regression analysis, and independent t-test. Results found that there was no correlation between personality traits and Facebook use, but age was a predictor for passive Facebook use. Neuroticism and openness were found to be positively correlated with active Instagram use but only openness was a predictor for active Instagram use. Neuroticism was found to be positively correlated and a predictor for active Twitter use. There were no gender differences for passive and active use across the three social media platforms. This paper discusses the possible reasons and implications for the findings.